Edward Meryon (1809-1880) and muscular dystrophy. - Emery, A E (1993)
Edward Meryon was an English physician of Huguenot stock. He studied medicine at University College, London, and his chief appointments were at St Thomas's Hospital and the London Infirmary for Epilepsy and Paralysis. In a communication to the Royal Medical and Chirurgical Society in December 1851, which was published in the Transactions of the Society the following year, he described in detail eight boys in three families with a disease later to be associated with the name of Duchenne. He was particularly impressed by the predilection for males and its familial nature. He appears to have been the first physician to make a systematic study of the disorder some years before Duchenne.